2011
DOI: 10.1055/s-0031-1297927
|View full text |Cite
|
Sign up to set email alerts
|

Classical and Emerging Roles of Vitamin D in Hepatitis C Virus Infection

Abstract: The risk of clinically-significant vitamin D deficiency increases at 25-hydroxyvitamin D levels below 20 ng/mL, according to the Institute of Medicine. By this standard, most cirrhotic hepatitis C virus (HCV)-positive patients and many non-cirrhotic patients are vitamin D deficient. The high prevalence of vitamin D deficiency among HCV patients is a cause for concern for several specific reasons. Classic studies established the importance of vitamin D and calcium in maintaining bone. Vitamin D's beneficial eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 90 publications
2
55
2
Order By: Relevance
“…Some studies examined the relationship between the vitamin D serum level and the progression of the disease in patients with chronic hepatitis C (5,10,12) , but this is a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies examined the relationship between the vitamin D serum level and the progression of the disease in patients with chronic hepatitis C (5,10,12) , but this is a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that vitamin D serum levels are inversely related to liver fibrosis, showing a relationship between the anti-inflammatory effects (10,14,20) . Thus, vitamin D deficiency could contribute to a (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Further, Bellamy showed that homozygotes genotype tt for a polymorphism at codon 352 were significantly lower among those with persistent hepatitis B infection compared to the other genotypes. Gutierrez et al (2011) reported that vitamin D improve immune responses of the host against infection with HCV. On the other hand, Garcıa-Martın et al (2013) showed that rs2228570TC polymorphism in vitamin D receptor gene is a good predictor of the outcome of PEG-IFN/RBV therapy in HCV patients.…”
Section: Vitamin Dmentioning
confidence: 99%
“…36 Vitamin D status was previously shown to be associated with SVR rates; however, it is not known whether vitamin D or other predictors of IFN response will consistently impact IFN-free therapy. 37 …”
Section: Costilla Et Almentioning
confidence: 99%